Human capital differences or labor market discrimination? The occupational outcomes of ethnic minorities in rural Guizhou (China) - Bente Castro Campos (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2013)
[Introduction ...] The objective of the first subchapter is to introduce the differences in labor market outcomes among ethnic groups in China and to acquaint the reader with some of the major determinants of these differences, notably ethnic status, human capital factors and geographic location. A frequently cited reason for lower labor market participation and higher rates of many ethnic minorities in agricultural employment is their comparatively lower educational attainment. Subchapter 1.2, therefore, particularly addresses educational differences among ethnic groups in China. The Chinese government recognized that ethnic minorities have been increasingly excluded from the job market and has taken several measures to overcome these inequalities. Subchapter 1.3 gives an overview of current preferential policies targeted at ethnic minorities and local governments in autonomous areas. Subchapter 1.4 then introduces the definitions of labor market discrimination and job preferences as well as presents the central research questions of this monograph. Subchapter 1.5 highlights the main scientific controversies. The last subchapter, 1.6, presents the organization of this monograph.
urn:nbn:de:gbv:3:2-26923
Keywords: 330